Manifestasi Karakter Peserta Didik melalui Metode Pendidikan Al-Hadits pada Mata Pelajaran Pendidikan Agama Islam - Gumilang, Ahmad Naufal; Nurdin, Muh Nur Islam (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose - This research aims to find out how the actualization of the Al-Hadith education method in Islamic religious education subjects shapes student character at SMPN 3 Pleret. Method - This research is descriptive qualitative research with observation and interview data collection techniques. The data that has been collected is then analyzed by reducing the data, presenting the data, and drawing conclusions. Findings - The research shows that the application of the Al-Hadith education method is carried out by the exemplary method, gentle method, deductive method, parable method, question and answer method, repetition method, demonstration method, experimental method, problem-solving method, discussion method, and praise/give joy method. The implications of applying the Al-Hadith education method include an open attitude to different views, the ability to respect others, and the strengthening of personal relationships between educators and students. In addition, learners are also more actively involved in religious activities and other activities in the community. The application of this method is hampered by the lack of Islamic religious education teacher resources, the lack of enforcement of school rules, and the weak control of parents and the community.Research Implications - This research recommends that the school, parents, and community strengthen their cooperation regarding the development of students' character education. This research is limited by descriptive analysis and limited data sources that only involve the school. Therefore, further research is needed to look at a broader perspective. In this case, the perspective of the community and parents.